In Vitro Antimicrobial Activity of Camel Urine Lactoferrin - Ahmad, K. A.; Jada, M. S.; Wurochekke, A. U. (Darul Yasin Al Sys, 2025)
Lactoferrin, an iron-binding glycoprotein found in various bodily fluids, is widely recognized for its broad-spectrum antimicrobial properties. This study evaluates the in vitro antibacterial and antifungal activity of lactoferrin isolated from camel urine against selected microbial strains. The purified lactoferrin demonstrated notable antibacterial efficacy, producing zones of inhibition ranging from 12–19 mm against Staphylococcus aureus, 10–16 mm against Bacillus subtilis, and 13–21 mm against Escherichia coli. Additionally, antifungal activity was observed against Candida albicans, with inhibition zones ranging from 11–18 mm. The antimicrobial mechanisms are attributed to iron sequestration and disruption of microbial cell membranes in bacteria, and inhibition of fungal growth via interference with cell wall synthesis and membrane integrity. These findings underscore the potential of camel urine-derived lactoferrin as a natural antimicrobial agent and contribute to the growing body of research exploring its biochemical and therapeutic properties.